Helicobacter pylori-induced gastric pathology: insights from in vivo and ex vivo models - Michael D. Burkitt; Carrie A. Duckworth; Jonathan Williams; D. Mark Pritchard (2017)
ABSTRACT Gastric colonization with Helicobacter pylori induces diverse human pathological conditions, including superficial gastritis, peptic ulcer disease, mucosa-associated lymphoid tissue (MALT) lymphoma, and gastric adenocarcinoma and its precursors. The treatment of these conditions often relies on the eradication of H. pylori, an intervention that is increasingly difficult to achieve and that does not prevent disease progression in some contexts. There is, therefore, a pressing need to develop new experimental models of H. pylori-associated gastric pathology to support novel drug development in this field. Here, we review the current status of in vivo and ex vivo models of gastric H. pylori colonization, and of Helicobacter-induced gastric pathology, focusing on models of gastric pathology induced by H. pylori, Helicobacter felis and Helicobacter suis in rodents and large animals. We also discuss the more recent development of gastric organoid cultures from murine and human gastric tissue, as well as from human pluripotent stem cells, and the outcomes of H. pylori infection in these systems.